Development economics : a critical introduction - Khan, Shahrukh Rafi (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"Following the 2007-2009 financial and economic crises, there has been an unprecedented demand among economics students for an alternative approach, which offers a historical, institutional and multidisciplinary treatment of the discipline. Economic development lends itself ideally to meet this demand, yet most undergraduate textbooks do not reflect this. This book will fill this gap, presenting all the core material needed to teach development economics in a one semester course, while also addressing the need for a new economics and offering flexibility to instructors. Rather than taking the typical approach of organizing by topic, the book uses theories and debates to guide its structure. This will allow students to see different perspectives on key development questions, and therefore to understand more fully the contested nature of many key areas of development economics. The book can be used as a standalone textbook on development economics, or to accompany a more traditional text"--
OCLC-licensed vendor bibliographic record.
Keywords: Development economics; Economic development; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Economic History; BUSINESS & ECONOMICS / Development / Economic Development